THE INFLUENCE OF COMPUTERIZED SYSTEMS ON EMPLOYEE WORK EFFECTIVENESS IN THE OFFICE OF THE REGIONAL ARCHIVES AND DOCUMENT LIBRARIES OF BARRU REGENCY - A. Ariyadi (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal